Influence of high anisotropy phase on the properties of hard–soft magnetic nanocomposite powders obtained by mechanical milling. (20th October 2018) - Hirian, R.; Bolinger, A.; Isnard, O.; Pop, V.
ABSTRACT: In materials with a good degree of magnetic interphase exchange coupling one has to consider both the extrinsic (microstructure) and intrinsic parameters (magnetisation, anisotropy, etc.) of the composite. This study investigates the feasibility of tuning the interphase exchange coupling condition by varying the anisotropy through the choice of the hard magnetic phase. The studied samples were produced by milling the hard magnetic phase along with 20 wt-% α -Fe powder for 6 h and subsequent annealing. The structure of the annealed powders was studied through X-ray diffraction and the magnetic properties of the nanocomposites were studied from demagnetisation curves and vs H plots in applied fields up to ±10 T.